1015. INULA RHIZOCEPHALA: Compositae. (21st January 2022) - Hind, Nicholas; Strange, Kit; King, Christabel
S ummary: Inula rhizocephala Schrenk (Compositae: Inuleae: Inulinae) is described and illustrated, together with a commentary on the discovery of Kew's current plant stock. Notes on cultivation, propagation, pests and diseases and availability are provided. It is highly likely that I. rhizocephala is an annual or biennial, or possibly a short‐lived perennial, since no perennating rootstock has been retained in either pot grown or Rock Garden plantings at Kew. The position of Inula rhizocephala in the genus, and within the tribe Inuleae subtribe Inulinae, is discussed. The author citation of the binomial Inula rhizocephala is also discussed as is the type material of I. rhizocephaloides, a synonym of I. rhizocephala, and aspects of the pollen presentation in the disc florets.